The Relationship Between Sub-Element of Integrity With Student Achievement Using Breathing - Shahidah, Hamzah; Muhammad Nubli, Abdul Wahab (The International Journal Research Publication's, 2015)
Integrity is one of the key elements for creating human resource quality. This is because of integrity has direct relationship with the development of the individual self. Lack of integrity can have widespread negative implications to the socioeconomic, politics and culture of a country. This article discusses about the breathing method used to measure the level of discipline and responsibility of an individual. The reason is that lack of integrity is one of the global issues which is becoming more serious and comes to no end. Breathing is a technique which enables an individual to control the flow of (in and out) the breath from the heart to the lungs smoothly, hence maximizing the amplitude of the person’s breathing. One of the methods identified which is able to measure the level of integrity of an individual is through respiration (biofeedback). Clinical research has been conducted on 50 respondents to view the individual breathing pattern rate of alteration. There are four breathing rates (BPM), those are: less than 8 BPM (very good), 9-11 BPM (good), 12-17 BPM (normal) and over 18 (not normal). Tests will be given to the respondents. The score for each test will be recorded. As a result, there is a stable relationship between breathing and student academic performance/achievement.